2017
DOI: 10.5114/hivar.2017.72025
|View full text |Cite
|
Sign up to set email alerts
|

Late presenters among newly diagnosed HIV-infected in Poland in 2006-2008

Abstract: Introduction: Assessment of incidence and factors associated with late vs. early human immunodeficiency virus (HIV) diagnosis among newly diagnosed patients referred to HIV treatment centres in Poland in the years 2006-2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The first Polish data collected from several centres for 1100 newly diagnosed HIV‐infected Polish patients in the 2006–2008 period showed that almost 50% were late presenters, with a median CD4 count at diagnosis of 355 cells/μL. Older age and male PWID were risk factors for delayed care entry . However, data from a smaller single‐centre study in Poland showed a very high (63%) incidence of late presentation for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first Polish data collected from several centres for 1100 newly diagnosed HIV‐infected Polish patients in the 2006–2008 period showed that almost 50% were late presenters, with a median CD4 count at diagnosis of 355 cells/μL. Older age and male PWID were risk factors for delayed care entry . However, data from a smaller single‐centre study in Poland showed a very high (63%) incidence of late presentation for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…This has been associated with improved prognosis and a decrease in mortality among HIV‐infected patients. Delayed HIV diagnosis and late care entry, linked to late presentation either with diagnosed AIDS or with low CD4 counts, remain major challenges for the control of the HIV/AIDS epidemic, with single‐centre data indicating that 50 to 63% of individuals were linked to care with either AIDS or a CD4 count < 350 cells/μL, despite expansion of test and treat efforts in Poland .…”
Section: Introductionmentioning
confidence: 99%
“…In a number of countries, including Poland, as many as 45–60% of patients are diagnosed with HIV/AIDS very late and at the stage of full-blown AIDS, usually with severe immunodeficiency and a CD4 T-lymphocyte count below 350 cells/mm 3 (late presenters). This requires quick and complex diagnostics and the fastest possible introduction of cART therapy [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%